Nutritional Support To Critically Ill Patients - A Comparative Study Between Branded and Homemade Preparations (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
We have evaluated the effectiveness of nutritional support to critically ill patients undergoing treatment in ICU. We provided commercially prepared branded food in one group and compared this, with those of homemade preparations. Fifty adult critically ill patients getting treatment in ICU aged between 20 to 60 years having no diabetes, hypertension, ischaemic heart disease and chronic renal failure, were scheduled for providing enterai nutritional support. They were randomly allocated into two groups. Group A (n=25) received commercially prepared branded food containing balanced food consisting of protein, fat, and carbohydrate in calculated proportion. The aim was to provide 2500 Kcal of energy per day for an average adult in his/her critical state. Group B (n=25) received homemade food preparations in proper proportion of those of group A and of equal calories. The purpose of the study was to assess, formulate and compare the efficacy, tolerability and cost effectiveness of homemade prepared food with commercially formulated branded food in maintaining nutritional status of critically ill patient in ICU. Patient's nutritional assessment was done before the commencement of nutritional support, Nutritional assessment was repeated weekly for successive two weeks. Group A showed better result than Group B, significant improvement has been observed also in group B and the differences between two groups are statistically not significant Both the methods of nutritional support were adequate and effective in maintaining the nutritional status. Considering the poor socioeconomic environment in an under developed country like Bangladesh, a less costly homemade preparation can be an effective alternative over the branded food.   Journal of BSA, Vol. 20, No. 1, January 2007 p.18-23